Development of weight and age-based dosing of daily primaquine for radical cure of vivax malaria - Taylor, WR; Hoglund, RM; Peerawaranun, P; Nguyen, TN; Hien, TT; Tarantola, A; von Seidlein, L; Tripura, R; Peto, TJ; Dondorp, AM; Landier, J; Nosten, FH; et al. (BioMed Central, 2021)
Background In many endemic areas, Plasmodium vivax malaria is predominantly a disease of young adults and children. International recommendations for radical cure recommend fixed target doses of 0.25 or 0.5 mg/kg/day of primaquine for 14 days in glucose-6-phosphate dehydrogenase normal patients of all ages. However, for many anti-malarial drugs, including primaquine, there is evidence that children have lower exposures than adults for the same weight-adjusted dose. The aim of the study was to develop 14-day weight-based and age-based primaquine regimens against high-frequency relapsing tropical P. vivax.